Pointwise Inequalities of Landau–Kolmogorov Type for Functions Defined on a Finite Segment - Babenko, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
For arbitrary t ∈ [0, 1], s ∈ [1, ∞], and A ≥ 2, we determine the unimprovable constant B for the inequality $$\left| {x\prime \left( t \right)} \right| \leqslant A\left\| x \right\|_{L_\infty \left[ {0,1} \right]} + B\left\| {x} \right\|_{L_s \left[ {0,1} \right]} .$$ .